1997
DOI: 10.1037/h0094482
|View full text |Cite
|
Sign up to set email alerts
|

Bizarreness of the dreams and daydreams reported by individuals with thin and thick boundaries.

Abstract: After completing a short form of the Boundary Questionnaire (Appendix A), 17 students with high scores indicative of thin boundaries and 13 students with low scores indicative of thick boundaries participated in a testing session in which they reported their "most recent dream'~ their "most recent daydream ", another "dream that really stands out'~ and another "daydream that really stands out." Dreams and daydreams were rated on three 8-point scales-Bizarreness, Dreamlikeness, and Emotionality-by two independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 6 publications
3
90
1
1
Order By: Relevance
“…Boundaries in the midrange of Hartmann's thin to thick continuum would therefore equate with Lile's clear boundaries. Hartmann's (1991) thin boundaries have been associated with higher levels of creativity (Hartmann, 1991); openness to experiences (McCrae, 1994;Van Hiel & Mervielde, 2004); the recall, vividness, and emotional intensity of dreams (Hartmann, Rosen, & Rand, 1998;Kunzendorf, Hartmann, Cohen, & Cutler, 1997); and unusual and mystical experiences (Hartmann, Harrison, & Zborowski, 2001). His thick boundaries have been linked to defensiveness (Hartmann, 1991), conservative ideology (Van Hiel & Mervielde, 2004), alexithymia (Hartmann, 1991), and obsessive tendencies (Hartmann, 1991).…”
Section: Identity Structurementioning
confidence: 97%
See 1 more Smart Citation
“…Boundaries in the midrange of Hartmann's thin to thick continuum would therefore equate with Lile's clear boundaries. Hartmann's (1991) thin boundaries have been associated with higher levels of creativity (Hartmann, 1991); openness to experiences (McCrae, 1994;Van Hiel & Mervielde, 2004); the recall, vividness, and emotional intensity of dreams (Hartmann, Rosen, & Rand, 1998;Kunzendorf, Hartmann, Cohen, & Cutler, 1997); and unusual and mystical experiences (Hartmann, Harrison, & Zborowski, 2001). His thick boundaries have been linked to defensiveness (Hartmann, 1991), conservative ideology (Van Hiel & Mervielde, 2004), alexithymia (Hartmann, 1991), and obsessive tendencies (Hartmann, 1991).…”
Section: Identity Structurementioning
confidence: 97%
“…The Boundary QuestionnaireÀ18 (BQ18; Kunzendorf et al, 1997) was utilized to assess boundaries. The instrument consists of 18 items along a 5-point Likert-type scale ranging from 0 (not at all true of me) to 4 (very much true of me).…”
Section: Boundariesmentioning
confidence: 99%
“…Hartmann (1991) proposed that nightmares partly result from thin psychological boundaries -separations between contents of the mind such as conscious and unconscious elements. Previous studies have supported that individuals with thinner psychological boundaries experience more unpleasant and bizarre dreams (i.e., nightmares) than those with thicker boundaries (Kunzendorf, Hartmann, Cohen, & Cutler, 1997;Miro & Martinez, 2005;Schredl, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…According to Singer and Bonnano, "night dreams turn out to be largely indistinguishable from the waking thoughts we experience when we let our minds wander in understimulated conditions" [26, p. 438]. Similarly, Kunzendorf et al have recently demonstrated that waking and dreaming mentation could be viewed on a continuum based upon subjects' waking boundary scores [20].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to these models, there exists an extensive empirical literature indicating that waking and dreaming mentation are continuous [3,[12][13][14][15][16][17][18][19][20]. Numerous studies have demonstrated that when waking conditions are altered to reduce both external sensory input and the conscious demand for cognitive process (relaxed wakefulness), the resultant free-floating thought is quite similar to, and may even surpass, dreaming mentation in its imagistic-hallucinatory quality [16,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%